CP-064 Effectiveness of new direct acting antivirals for chronic hepatitis C depending on genotype in real medical practice. (25th February 2017) - Molina, M; Moreno, F; Jimenez, I; Gonzalez, A; Jimenez, C; Rossignoli, A; Freire, M; Herrero, A
Abstract : Background: New direct acting antivirals (DAAs) for chronic hepatitis C achieve a sustained virologic response (SVR) above 90% in clinical trials. SVR is defined as undetectable HCV RNA 12 weeks after treatment completion (SVR12). Purpose: Our aim was to evaluate the effectiveness of treatment depending on the genotype of the virus with new DAAs for chronic hepatitis C in real medical practice. Material and methods: This was an observational retrospective study. Data were obtained from 922 patients with HCV treated with DAAs from April 2015 to February 2016. All patients had finished treatment and the results of HCV RNA levels 12 weeks post-treatment were available. We considered that the drug was effective if the patient achieved SVR12. Data collected were: age, gender, HIV coinfection, prior treatment experience, genotype, hepatic fibrosis stage, DAAs regimen and HCV RNA level. Results: We included 922 patients. 57% were men. Median age was 59 years. 237 (26%) patients were HIV coinfected. Regarding previous treatment, 94 (10%) had been treated with protease inhibitors, 531 (56%) were naïve, 139 (15%) were non-responders, 132 (14%) were relapsers, 89 (10%) were partial responders and 31 (3%) patients had no data. The most frequent genotype was 1b. The hepatic fibrosis stage was F4 in 304 (33%), F3 in 201 (22%), F2 in 359 (39%) and F1 in 52 (6%). The treatment regimens were: dasabuvir+paritaprevir/ritonavir+ombitasvir±ribavirine 12 weeks in 159; dasabuvir+paritaprevir/ritonavir+ombitasvir±ribavirine 24 weeks in 6; sofosbuvir+ledipasvir±ribavirine 8–12 weeks in 463; sofosbuvir+ledipasvir±ribavirine 24 weeks in 165; sofosbuvir+daclatasvir±ribavirine 12 weeks in 46; sofosbuvir+daclatasvir±ribavirine 24 weeks in 29; paritaprevir/ritonavir+ombitasvir+ribavirine 12 weeks in 22; paritaprevir/ritonavir+ombitasvir+ribavirine 24weeks in 1; sofosbuvir+simeprevir+ribavirine 12 weeks in 3; sofosbuvir+simeprevir+ribavirine 24 weeks in 1; sofosbuvir+ribavirine 12 weeks in 1; and sofosbuvir+ribavirine 24 weeks in 3. RSV12 was achieved by 894 (97%) patients. The effectiveness based on genotype was 98% in genotype 1, 95% in genotype 4 and 86% in genotype 3. Conclusion: Results of effectiveness based on RVS12 were similar to results obtained in clinical trials. Genotype 1 had better results than the other genotypes, and genotype 3 had the worst results. No conflict of interest